α-Glucosidase inhibitor compounds of Uncaria sclerophylla leaves’ most active chromatography fraction: In vitro, in silico, and ADMET analysis - Nita Triadisti, Berna Elya, Muhammad Hanafi, Najihah Mohd Hashim, Adha Dastu Illahi (Journal of Applied Pharmaceutical Science, 2025)
Diabetes mellitus is a noncontagious disease and a leading cause of death globally. It is characterized by a disorder in glucose metabolism, resulting in uncontrolled hyperglycemia. Various classes of type 2 DM therapy have demonstrated therapeutic benefits, but the global incidence continues to rise, necessitating the discovery of new therapeutic agents for type 2 diabetes. This study aims to determine the most potent Uncaria sclerophylla Roxb leaf fraction as an α-Glucosidase inhibitor, accompanied by the Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) profile and interaction mechanism of compounds in U. sclerophylla leaves. Extraction involved using four-graded maceration to obtain compounds with different polarities, followed by column chromatography of the most potent extract. The bioassay utilized spectrophotometry techniques and a microplate reader. liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QToF-MS) was employed to identify compound profiles in the most promising fractions, followed by in silico analysis of ADMET profiles and interaction mechanisms. The study found that ethyl acetate and methanol extract potency in α-Glucosidase inhibition with an IC50 of 75.75 and 42.70 μg/ml, respectively. The most promising fraction, USMeth5, was obtained through column chromatography with better activity than acarbose with an IC50 of 22.85 μg/ml. LC-QToF-MS analysis revealed the presence of various phenolic compounds, flavonoids, and alkaloids in USMeth5, along with ADMET profiles and interaction mechanisms in silico. The results of the study have successfully unveiled the potential of U. sclerophylla leaves and the most active fractions to be developed as a promising antidiabetic.
Keywords: Uncaria sclerophylla Roxb, α-Glucosidase, four-graded maceration, column chromatography, LC-MS/MS compound profiling